Malignant Care: Affects and Labor in Anita Nair’s Ladies Coupé (2001) - Pujarinee Mitra (Humanities, 2023)
Anita Nair’s Ladies Coupé (2001) is about six women who meet in an express train’s compartment in southern India. One of these women, Akhila, is the narrator of the novel, while we hear the voices of the other women only when they narrate their stories in first person to Akhila. The way the women tell these stories one by one is in the spirit of empowering Akhila, who is portrayed as a woman bound within heteronormative ideas of coupledom and gender-based expectations of care labor within patriarchal families. The women also encourage her, by example, to question the accepted ethical model of feminist practice within an already unethical patriarchal structure of society. This encouragement happens, I argue, as they recount instances of the self-acknowledged unethical care practices through which they have affectively resisted different forms of violence within the upper caste, patriarchal, heteronormative family structure. These forms of violence are intersectional as they are based on overlapping identities of caste, age, and gender.